ANALISIS LINGKUNGAN PENGENDAPAN BATUAN BERUMUR JURA DI KEPULAUAN MISOOL, PAPUA BERDASARKAN FOSIL MAKRO - Hasibuan, Fauzi (Jurnal Geologi dan Sumberdaya Mineral, 2010)
Paleoecological analysis and depositional history of the marine Jurassic to Early Cretaceous, Toarcian - Early Berriasian, strata cropped out at the southeast coast and the islets of Misool are discussed. The macrofossil fauna subdivides the stratigraphy of the areas into 4 assemblages. In stratigraphic ascending order these are 1. Bivalve - Ammonite Assemblage with a Bositra ornate, 2. Belemnite – Bivalve Assemblage 3. Ammonite – Bivalve - Belemnite Assemblage and 4. Bivalve - Ammonite- Belemnite Assemblage.Bivalves occur in the whole section of Toarcian - Berriasian, while belemnite made its first appearance in the Early Callovian time and continued to the Cretaceous. The Ammonite plays an important role and is presented only in Assemblages 1, 3 and 4.The paleoenvirontmental deposition of the Jurassic to Early Cretaceous of the Misool Archipelago was likely related to a continental shelf and continental slope of low energy. The presence of a Bositra ornati Sub-assemblage indicates a restricted basinal anoxic condition for a short period in the Aalenian Stage. PaleogeographIcally, the Misool Archipelago in the Jurassic time was likely located at the northern margin of the Gondwana land or at the southern coast of the Tethyan Sea.Keywords : Jurassic, Early Cretaceous, Toarcian, Early Barriasian, Misool